The Dick Pic: Harassment, Curation, and Desire. (April 2019) - Paasonen, Susanna; Light, Ben; Jarrett, Kylie
The combined rise of digital photography and social media has expanded what might be considered photo worthy. Among the pouting selfies and food stuffs of the day exists the ubiquitous dick pic. The mainstream media generally focuses on dick pics of the unsolicited kind, which, negatively positioned, are commonly associated with heterosexual harassment. Considering the ubiquity of dick pics across apps and platforms, research on the topic nevertheless remains scarce. In this article, we examine the dick pic as an online communicative form, first considering how it manifests the ability to harass and then moving beyond this dominant framing to analysis of contexts where such images are collated, expected, and sought after. Through this analysis of dick pics as figures and actors of harassment, curation, and desire, we demonstrate the simultaneous tenacity and flexibility of their meanings in connection with the dynamics of consent and non-consent, intimacy and distance, and complex circuits of desire. We further address the role of platforms, apps, and app stores, via their community standards and terms of use, in shaping the nature, and presence, of dick pics, and discuss the affective and communicative functions that these affordances serve (or fail to serve). Our analysis of three key modes of engagement with dick pics demonstrates the ambiguity and multiple valences of the phenomenon addressed.